Greater Similarity Between L1 and L2’s Brain Network in Adults Than in Children - Cao, Fan; Fan, Yuyu; Yan, Xin; Chen, Wuying; Dodson-Garrett, Maddie; Spray, Gregory J.; Wang, Zhao; Deng, Yuan (Frontiers in Neuroscience, 2022)
It has been documented that processing L2 and L1 engages a very similar brain network in bilingual adults. However, it is not known whether this similarity is evident in bilingual children as well or it develops with learning from children to adults. In the current study, we compared brain activation in Chinese-English bilingual children and adults during L1 and L2 processing. We found greater similarity between L1 and L2 in adults than in children, supporting the convergence hypothesis which argues that when the proficiency of L2 increases, the L2’s brain network converges to the L1’s brain network. We also found greater differences between adults and children in the brain for L2 processing than L1 processing, even though there were comparable increase in proficiency from children to adults in L1 and L2. It suggests an elongated developmental course for L2. This study provides important insights about developmental changes in the bilingual brain.